Melatonin Alleviates Renal Injury in Mouse Model of Sepsis - Chen, Liyang; Han, Zhijian; Shi, Zhiguang; Liu, Chao; Lu, Qiulun (Frontiers in Pharmacology, 2021)
Melatonin (N-acetyl-5-methoxytryptamine; MLT) has been shown to have a renal-protective effect against kidney injury. However, the mechanisms underlying the protective role of MLT in sepsis-induced renal injury remain to be revealed. In this study, MLT alleviated renal dysfunction with increase of BUN (Blood Urea Nitrogen) and SCR (Serum Creatinine) and reduction of fibrosis in CLP (Cecal Ligation Puncture) model. RNA-seq analysis showed that MLT repressed the oxidant stress in response to kidney injury. Our in vitro study showed MLT suppresses LPS-induced accumulation of ROS (Reactive Oxygen Species) production via SOD2 downregulation and Nox4 upregulation in HK-2 cells. Furthermore, we found that MLT alleviated the inflammatory response, with the mRNA level reduction of Il-1α, Il-1β, Mcp-1, and Tgf-β1. Taken together, in evaluating the therapeutic effect of MLT on sepsis-induced acute kidney injury, the results showed that MLT alleviated renal damage by regulating the production of ROS.